Chronic Multisymptom Illness Among Female Veterans Deployed to Iraq and Afghanistan. Issue 4 (April 2015) - Mohanty, April F.; Muthukutty, Anusha; Carter, Marjorie E.; Palmer, Miland N.; Judd, Joshua; Helmer, Drew; McAndrew, Lisa M.; Garvin, Jennifer H.; Samore, Matthew H.; Gundlapalli, Adi V.
Abstract : Background: Chronic multisymptom illness (CMI) may be more prevalent among female Operation Enduring Freedom/Operation Iraqi Freedom/Operation New Dawn (OEF/OIF/OND) deployed Veterans due to deployment-related experiences. Objectives: To investigate CMI-related diagnoses among female OEF/OIF/OND Veterans. Research Design: We estimated the prevalence of the International Classification of Disease-9th edition-Clinical Modification coded CMI-related diagnoses of chronic fatigue syndrome, fibromyalgia (FM), and irritable bowel syndrome (IBS) among female OEF/OIF/OND Veterans with Veterans Health Administration (VHA) visits, FY2002–2012 (n=78, 435). We described the characteristics of female Veterans with and without CMI-related diagnoses and VHA settings of first CMI-related diagnoses. Results: The prevalence of CMI-related diagnoses among female OEF/OIF/OND Veterans was 6397 (8.2%), over twice as high as the prevalence 95, 424 (3.9%) among the totality of female Veterans currently accessing VHA ( P <0.01). There were statistically significant differences in age, education, marital status, military component, service branch, and proportions of those with depression and/or post-traumatic stress disorder diagnoses across females with and without CMI-related diagnoses. Diagnoses were mainly from primary care, women's health, and physical medicine and rehabilitation clinics. Conclusions: CMI-related diagnoses were more prevalent among female OEF/OIF/OND Veterans compared with all female Veterans who currently access VHA. Future studies of the role of mental health diagnoses as confounders or mediators of the association of OEF/OIF/OND deployment and CMI are warranted. These and other factors associated with CMI may provide a basis for enhanced screening to facilitate recognition of these conditions. Further work should evaluate models of care and healthcare utilization related to CMI in female Veterans. Abstract : Supplemental Digital Content is available in the text.